The production of short chain fatty acid and colonic development in weaning piglets. Issue 5 (27th July 2019) - Zhou, Zirui; Zhang, Jie; Zhang, Xianlian; Mo, Shilan; Tan, Xian; Wang, Lixia; Li, Jianzhong; Li, Yali; Ding, Xueqin; Liu, Xianyong; Ma, Xingqun; Yang, Huansheng; et al.
Abstract: Weaning process widely affects the small intestinal structure and function in piglets, while the responses of large intestine to weaning stress are still obscure. The purpose of this study was to determine the developmental changes (i.e., short chain fatty acids (SCFAs) concentrations, growth parameters, crypt‐related indices and antioxidant capacity) in colon of piglet during weaning. Forty piglets were weaned at day 21 and euthanized to collect colonic tissues and digesta samples on day 0, 1, 3, 7 and 14 post‐weaning ( n = 8). Piglet growth performance was improved ( p < .001) on day 7 and 14 post‐weaning. The concentrations of acetate, propionate, butyrate, valerate, isobutyrate, isovalerate and total SCFAs were higher ( p < .001) during the late post‐weaning period. The mRNA abundances of SCFAs transporters were greater ( p < .001) on day 7 and 14. The absolute and relative weights, absolute length and perimeter of colon were greater ( p < .001) on day 7 and 14. Similarly, post‐weaning increases ( p < .001) in colonic crypt depth and Ki67 positive cells numbers per crypt were observed during the same period. Colonic crypt fission indices decreased ( p < .01), while total crypt numbers increased ( p < .001) on day 14 after weaning. Moreover, total SCFAs concentration was significantly associated with colonic growth parameters and Ki67 cells/crypt ( p < .001). In addition, catalase content was decreased on day 3, 7, and 14, whereas, the concentrations of total superoxide dismutase (T‐SOD) and manganese‐containing superoxide dismutase (MnSOD) were higher ( p < .05) on day 1 and 3 post‐weaning. These results showed that weaning process has a significant effect on colonic growth and development, which might be associated with the change of SCFAs concentrations in colon.